2014
DOI: 10.1155/2014/362725
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury by Radiographic Contrast Media: Pathogenesis and Prevention

Abstract: It is well known that iodinated radiographic contrast media may cause kidney dysfunction, particularly in patients with preexisting renal impairment associated with diabetes. This dysfunction, when severe, will cause acute renal failure (ARF). We may define contrast-induced Acute Kidney Injury (AKI) as ARF occurring within 24–72 hrs after the intravascular injection of iodinated radiographic contrast media that cannot be attributed to other causes. The mechanisms underlying contrast media nephrotoxicity have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 194 publications
1
112
0
1
Order By: Relevance
“…A similar finding was reported in the study by Andreucci et al, which revealed a higher incidence of renal failure in patients injected with a greater volume of contrast agent or multiple injections of contrast agent 72 hours after endovascular treatment. 16 Regarding the infrapopliteal arteries subjected to endovascular treatment, we found that angioplasty was more commonly performed in the peroneal and posterior tibial arteries in group 2 but in the anterior tibial artery in group 1. Kawarada et al 17 measured the tissue perfusion pressure in the forefoot and on the plantar surface of patients who underwent single angioplasty of the anterior tibial or posterior tibial arteries.…”
Section: Discussionmentioning
confidence: 77%
“…A similar finding was reported in the study by Andreucci et al, which revealed a higher incidence of renal failure in patients injected with a greater volume of contrast agent or multiple injections of contrast agent 72 hours after endovascular treatment. 16 Regarding the infrapopliteal arteries subjected to endovascular treatment, we found that angioplasty was more commonly performed in the peroneal and posterior tibial arteries in group 2 but in the anterior tibial artery in group 1. Kawarada et al 17 measured the tissue perfusion pressure in the forefoot and on the plantar surface of patients who underwent single angioplasty of the anterior tibial or posterior tibial arteries.…”
Section: Discussionmentioning
confidence: 77%
“…1 The use of CM has risen in recent years due to an increase in radiographic procedures, and this coupled with an aging population already suffering from diabetes and cardiovascular/renal diseases (including chronic kidney disease, hypertension, hypotension, advanced congestive heart failure, and compromised left ventricular performance) has led to an increase in the incidence of CI-AKI. [2][3][4][5][6][7][8] CI-AKI…”
Section: Introductionmentioning
confidence: 99%
“…5 A reduction in the effective circulating blood volume in the elderly may be due to congestive heart failure, compromised left ventricle systolic performance, and prolonged hypotension; under such circumstances, renal vasoconstriction is accentuated, thereby making renal ischemia more severe. 3,181 Measures to prevent CI-AKI that may be useful for physicians include: 1) discontinuation of potentially nephrotoxic drugs (aminoglycosides, vancomycin, amphotericin B, metformin, and nonsteroidal anti-inflammatory drugs 2 ; 2) choice of the least nephrotoxic radiocontrast agent (iohexol is less nephrotoxic than diatrizoate; iodixanol and iopamidol seem the least nephrotoxic agents 10 ; 3) use of the lowest dosage possible of CM (some formulas have been suggested to calculate the dosage that is least dangerous for the kidney [182][183][184][185] ; 4) adequate hydration of the patient 186,187 by IV infusion of 0.9% saline at a rate of ~1 mL/kg body weight/hr or 154 mEq/L infusion of sodium bicarbonate as a bolus of 3 mL/kg bw/hr for 1 hour; 188 5) short-duration pretreatment with antioxidants, such as N-acetylcysteine (an oral dose of 600 mg twice daily the day before and the day of procedure 10 or an IV dose of 150 mg/kg over half an hour before the procedure or 50 mg/kg administered over 4 hours; 189 6) Nebivolol (5 mg/d for 1 week or 5 mg every 24 hours for 4 days). 190,191 Summary and future perspectives CI-AKI is a leading cause of hospital-acquired kidney failure and no doubt will continue to increase with the increase in use of radiological procedures.…”
mentioning
confidence: 99%
“…AKI induced by renal IRI may cause high morbidity and mortality in patients subjected to these surgeries [2,5,6]. Unfortunately, because of the poor understanding of renal IRI, no sufficient therapeutic approaches were available for patients with renal IRI until recently [7,26]. Therefore, we believe that the results of our study are promising, as a single dose of butyrate pretreatment protected kidneys from renal IRI, by significantly inhibiting inflammatory responses and tubular apoptotic death.…”
Section: Discussionmentioning
confidence: 73%